Pengaruh Efisiensi, Pertumbuhan Penjualan, Modal Kerja, dan Umur Perusahaan terhadap Profitabilitas Perusahaan: (Studi Empiris Pada Perusahaan yang Menerbitkan Saham Syariah yang Terdaftar dalam Jakarta Islamic Index 70 (JII70) Periode 2019 – 2023) - Arika Nur’Aini; Desy Mariani (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to determine the effect of efficiency, sales growth, capital working, and firm age on firm profitability in Companies publish syariah stock that listed on the Jakarta Islamic Index 70 (JII70) for the 2019 – 2023 period of 70 companies. The data used in this study were obtained from financial statement data and annual reports. The population in this study are companies that publish syariah stock that listed on the Jakarta Islamic Index 70 (JII70). The sampling technique used was purposive sampling method and obtained 185 sample data from 37 companies. The analysis technique used in this study is multiple linear regression analysis using the Statistical Package for the Social Sciences (SPSS) version 22. The results of this study indicate that efficiency and sales growth have a positive effect on firm profitabillity, capital working have a negative effect on firm profitability, and firm age has no effect on firm profitability.